Pengaruh Growth Opportunity, Return On Aset (ROA) Dan Debt To Equity Ratio (DER) Terhadap Nilai Perusahaan Pada Subsektor Rokok Yang Terdaftar Di BEI - Triati Putri; Nurulrahmatiah, Nafisah; Muniarty, Puji (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the effect of Growth Opportunity, Return On Asset (ROA), and Debt to Equity Ratio (DER) on company value in the cigarette sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. The research method used is quantitative with an associative approach. Data was obtained through documentation of financial reports of cigarette sub-sector companies listed on the IDX. The data analysis technique used multiple linear regression analysis with the help of SPSS version 26. The results of the study indicate that partially Growth Opportunity and Debt to Equity Ratio do not have a significant effect on company value. Meanwhile, Return On Asset (ROA) has a significant effect on company value. Simultaneously, these three variables have a significant effect on company value. This finding shows that profitability reflected in ROA is an important factor influencing investor perception and company value, while growth opportunities and capital structure do not directly affect the value of cigarette sub-sector companies.